Fiscal effects of accession in the new member states - Hallet, Martin; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2004)
The paper looks at the evidence on the widespread hypothesis in the academic literature and by some of the new Member States' governments that accession will bring about fiscal strains and requires higher budget deficits. It starts by calculating the expected new Member States' payments from the EU budget and looks at the issues of additionality and national co-financing of EU funds. Other possible fiscal effects from accession are briefly discussed.
Economic Papers